2015
DOI: 10.1111/ajt.13226
|View full text |Cite
|
Sign up to set email alerts
|

National Healthcare Delivery Systems Influence Lung Transplant Outcomes for Cystic Fibrosis

Abstract: Successful lung transplantation (LTx) depends on multiple components of healthcare delivery and performance. Therefore, we conducted an international registry analysis to compare post‐LTx outcomes for cystic fibrosis (CF) patients using the UNOS registry in the United States and the National Health Service (NHS) Transplant Registry in the United Kingdom. Patients with CF who underwent lung or heart–lung transplantation in the United States or United Kingdom between January 1, 2000 and December 31, 2011 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…In Canada, universal healthcare provides all individuals with the opportunity to access medical services across the country; in the US, differing health insurance coverage impacts access to medical care and costs of care and is related to socioeconomic status (SES). (30;33) Indeed we observed health insurance status in the US had a differential effect on the risk of death for individuals living with CF compared to Canada. Interestingly, there was no statistically significant difference in risk of death among Canadians and those in the US with “other” insurance (which was comprised primarily of individuals with private coverage).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In Canada, universal healthcare provides all individuals with the opportunity to access medical services across the country; in the US, differing health insurance coverage impacts access to medical care and costs of care and is related to socioeconomic status (SES). (30;33) Indeed we observed health insurance status in the US had a differential effect on the risk of death for individuals living with CF compared to Canada. Interestingly, there was no statistically significant difference in risk of death among Canadians and those in the US with “other” insurance (which was comprised primarily of individuals with private coverage).…”
Section: Discussionmentioning
confidence: 68%
“…For instance, median survival post-lung transplant is longer in Canadian CF patients compared to published studies of US CF patients. (32) (33) Although the LAS has been associated with shorter waiting times and improved transplant survival(35), and the number of patients with CF listed for lung transplantation has increased since its implementation, the proportion who have received a transplant has decreased. (36) In addition, Merlo et al showed that CF patients transplanted since the LAS was implemented had a higher risk of death compared to CF patients transplanted in the pre-LAS period.…”
Section: Discussionmentioning
confidence: 99%
“…Patients not completing high school and those residing in ZIP codes with lowest median household income also experienced higher odds (2.37 and 1.39, respectively) of not being accepted for lung transplant. Similarly, a registry analysis of CF patients who underwent lung transplantation in the United States or the United Kingdom between 2000 and 2011 showed that US Medicare/Medicaid insurance was associated with worse survival after lung transplantation compared to US private insurance and UK National Health System (p < 0.001) [130].…”
Section: Medical Carementioning
confidence: 99%
“…La publicación de Merlo y cols 249 , sobre la influencia de los seguros médicos en el TP por FQ, reporta que la necesidad de oxigenoterapia previa al TP es del 72.8 % en los pacientes de Reino Unido y del 83,8% en los Estados Unidos de Norteamerica.…”
Section: Características Demográficasunclassified